Environmental, Social, and Governance (ESG), Green Innovation, and Firm Value in Indonesia: A Study of Companies Operating in Energy Sector for The Year 2020 - 2024 - Hunaifa Hunaifa; Anis Chariri (Diponegoro Journal of Accounting, 2026)
This study examines the relationship between Environmental, Social, and Governance (ESG) and firm value, with particular attention to the mediating role of green innovation. The research aims to: (1) analyze the influence of ESG pillars on green innovation, (2) evaluate the impact of ESG pillars on firm value, (3) assess the effect of green innovation on firm value, and (4) investigate whether green innovation mediates the relationship between ESG pillars and firm value. A quantitative approach is employed using panel data from 12 companies observed over the 2020–2024 period, resulting in 60 firm-year observations. The study utilizes secondary data obtained from sustainability reports, ESGi, and Bloomberg databases. ESG performance is measured through environmental, social, and governance scores, while green innovation is proxied by PROPER ratings and firm value is measured using Tobin’s Q. The empirical results indicate that the governance pillar is the only ESG dimension that significantly and positively affects firm value. Moreover, governance performance also influences firm value indirectly through green innovation. The findings further show that green innovation positively contributes to firm value and partially mediates the relationship between governance performance and firm value.